Формування репозитарію біобібліографічних даних: до історіографії питання - Філіппова, Наталя (Видавництво Львівської політехніки, 2020)
The results of historiographical analysis of the problems of formation and functioning of consolidated electronic data repositories on the example of a repository of biobibliographical information are presented. The main directions of scientific researches, devoted to separate aspects of creation of open access resources, are defined.
Keywords: біобібліографія; консолідовані інформаційні ресурси; репозитарій біобібліографічних даних